2023
DOI: 10.18280/ijsdp.180529
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Performance, Green Strategy, Financial Performance Effect on Carbon Emissions Disclosure: Evidence from High Polluting Industry in Indonesia

Abstract: The purpose of this study is to investigate the impact of carbon performance, green strategy and financial performance on carbon emissions disclosure based on GRI 305: Emissions, of five polluting industrial sectors in Indonesia during period of 2017 to 2020. Factors affect carbon disclosure show conflicting results like positive, negative, and also no affect. All these findings in this paper may provide a new insight about what factor that affect pollutant industry disclose their carbon information. Pollutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…The findings of this research coincide with the findings of previous research which found that green strategies provide encouragement for companies to disclose their activities in reducing carbon emission levels [21]. Although there are many reasons for companies to reduce carbon emissions, a green strategy is one of the most prominent ways.…”
Section: Resultssupporting
confidence: 88%
“…The findings of this research coincide with the findings of previous research which found that green strategies provide encouragement for companies to disclose their activities in reducing carbon emission levels [21]. Although there are many reasons for companies to reduce carbon emissions, a green strategy is one of the most prominent ways.…”
Section: Resultssupporting
confidence: 88%
“…Ordinary least squares (OLS) regression is a commonly used method [39][40][41][42][43] for estimating coefficients in linear regression equations. The OLS method is often used [44,45] Environmental performance is the dependent variable that reveals the carbon dioxide emissions of companies and is calculated as CO2 equivalent direct emissions (Scope 1) divided by market capitalization multiplied by 1000. Market capitalization is an indicator obtained by multiplying the number of shares of a company by the price of one share.…”
Section: Methodsmentioning
confidence: 99%
“…More scientific evidence shows that carbon emissions, which are the leading cause of global warming, are a severe threat to life both economically, socially, and environmentally [9][10][11][12][13]. Disclosure of carbon emissions needs to be conveyed to stakeholders as evidence of efforts by corporations to support the reduction of greenhouse gas (GHG) emissions.…”
Section: Introductionmentioning
confidence: 99%